The international council of women in Spain during the first third of the twentieth century: reception, influence and exchanges. - Lisa, Sandra Blasco (Women's History Review, 2023)
This article explores the connections between the International Council of Women (ICW) and some Spanish women during the first third of the twentieth century. It proposes a broad interpretation of historical feminisms that permits a better understanding of the different forms of connection between these women. On the one hand, it looks at informal networks (affinities relations, friendships, individual contacts, etc.) and formal networks (associations), while on the other, it includes other examples of feminisms that developed in southern Europe.